1992
DOI: 10.1101/gad.6.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of G alpha 4, a G-protein subunit required for multicellular development in Dictyostelium.

Abstract: The Dictyostelium G^4 gene encodes a G-protein a subunit that is primarily expressed during the muhicellular stages of development. g^4 null mutants, created by gene disruption, show aberrant morphological differentiation, reduced levels of prespore gene expression, and a loss of the ability to produce spores. These developmental phenotypes can be rescued by complementation with the wild-type gene. Cells that overexpress the G"4 gene {0^4^^*^) also show reduced spore production but display an aberrant morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
165
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 140 publications
(172 citation statements)
references
References 45 publications
7
165
0
Order By: Relevance
“…In the migrating slug, ERKJ/lacZ-expressing cells are scattered throughout the organism with a higher concentration toward the posterior (Fig. 8E), a pattern that has been previously seen for Ga4 (32,33) or the gene encoding the phosphotyrosine phosphatase PTP2 (42). As culmination initiates, staining is more concentrated in the anterior tip and the cells migrating to form the lower cap of the sorus (Fig.…”
Section: ]) (See Below)supporting
confidence: 69%
See 4 more Smart Citations
“…In the migrating slug, ERKJ/lacZ-expressing cells are scattered throughout the organism with a higher concentration toward the posterior (Fig. 8E), a pattern that has been previously seen for Ga4 (32,33) or the gene encoding the phosphotyrosine phosphatase PTP2 (42). As culmination initiates, staining is more concentrated in the anterior tip and the cells migrating to form the lower cap of the sorus (Fig.…”
Section: ]) (See Below)supporting
confidence: 69%
“…We assume that the spatial pattern reflects the expression pattern of the late promoter since RNA blots with the ERKJ/ERK1 construct show a developmentally regulated shift in transcript size, as does the endogenous ERK1 mRNA. Previous studies in our laboratory have shown that the ,B-Gal produced from our constructs is unstable (25,32,33,43). Several other genes that have been studied in our laboratory have a similar ALC-like pattern of expression during the multicellular stages and are also expressed during growth, such as Ga4 and PTP1 (32,33,43) or rasD, which shows a prestalk-enriched pattern of expression and is also expressed in ALCs (25).…”
Section: ]) (See Below)mentioning
confidence: 65%
See 3 more Smart Citations